Effects of Manganese From a Commercial Multi–Trace Element Supplement in a Population Sample of Canadian Patients on Long‐Term Parenteral Nutrition. Issue 4 (24th July 2012) - Abdalian, R.; Saqui, O.; Fernandes, G.; Allard, J. P.
Abstract : Background: Long‐term parenteral nutrition (PN) can be associated with micronutrient deficiency or toxicity depending on supplementation. Recently, hypermanganesemia and potential neurological toxicity were reported. The aim of this study was to assess the effect of manganese supplementation in a sample of patients on long‐term PN receiving manganese (Mn) as part of a multi–trace element (TE) supplement. Methods: A convenience sample of 16 patients underwent clinical and blood biochemical measurements as well as magnetic resonance imaging (MRI) of the brain. Descriptive statistics were performed. Results: The mean daily Mn supplementation was 7.28 ± 0.97 µmol/d (400 ± 53 µg/d), which was within the American Medical Association Nutrition Advisory Group guidelines of 2.73–14.56 μmol/d (150–800 µg/d) but exceeded the American Society for Parenteral and Enteral Nutrition (A.S.P.E.N.) 2002 recommendations of 1.09–1.82 µmol/d (60–100 µg/d). The mean whole blood Mn level was 1.38 ± 0.29 times the upper limit of normal (ULN), and 8 of 14 patients with blood measurements had Mn levels above ULN. On MRI, 81% of patients had high signals on T1‐weighted images assumed to be Mn deposits in their basal ganglia. Two patients with positive MRI (15%) had a clinical diagnosis of Parkinson disease. Multiple neuropsychiatric complaints were reported, including depression (66%), lack of concentration (42%), memory disturbances (17%), and gait instability (8%). Conclusion: These results suggest that Mn status is elevated in these patients. Manganese supplementation should be used with caution in patients receiving long‐term PN, and attention should be paid to the Mn content of multi‐TE supplements.